Penerapan Edukasi Berbasis Theory of Planned Behavior Untuk Meningkatkan Kepatuhan Pengobatan, Nutrisi, dan Pencegahan Penularan pada Pasien Tuberkulosis (Tb) Di Puskesmas Batang 2 - Sulistiyoningsih Sulistiyoningsih; Rahayu Winarti (Journal of Health, Medical, and Psychological Studies, 2026)
Here is the high-quality academic English version: Tuberculosis (TB) is a communicable disease that affects not only patients’ physical health but also their psychological well-being. Non-adherence to treatment, inadequate nutritional intake, and insufficient transmission-prevention behaviors remain significant challenges in TB control efforts. Education grounded in the Theory of Planned Behavior (TPB) is considered capable of influencing attitudes, subjective norms, and perceived behavioral control, thereby promoting more optimal health behavior changes. This study aimed to determine the effectiveness of TPB-based education in improving treatment adherence, nutritional fulfillment, and transmission-prevention practices among TB patients at Batang 2 Primary Health Center. A case study design was employed involving five TB patients undergoing the intensive phase of treatment. The intervention consisted of four face-to-face educational sessions over a two-week period, supplemented by twice-daily SMS/WhatsApp reminders. Data were collected using adherence observation sheets, nutritional questionnaires, and TPB observation forms, and were analyzed by comparing pre- and post-intervention scores. The results demonstrated an increase in adherence scores from 5–6 to 7–9 across all respondents. TPB-based education proved effective and is recommended as a nursing strategy to support TB control in primary healthcare settings.